Cognitive Development in Chimpanzees - Matsuzawa, Tetsuro; Tomonaga, Masaki; Tanaka, Masayuki; SpringerLink (Online service) (Tokyo : Springer Tokyo, 2006)
From an evolutionary perspective, understanding chimpanzees offers a way of understanding the basis of human nature. This book on cognitive development in chimpanzees is the first of its kind to focus on infants reared by their own mothers within a natural setting, illustrating various aspects of chimpanzee cognition and the developmental changes that accompany them. The subjects of this book are chimpanzees of three generations inhabiting an enriched environment as well as a wild community in West Africa; and phenomena such as face recognition, concept formation, object manipulation, tool manufacture and use, decision making, learning, communication, self-awareness, intentionality, understanding others$1 (Bminds, cooperation, deception, altruism, and reciprocity observed within these groups are reported herein. Unique approaches both in the field and in the laboratory go hand in hand to illustrate the cognitive world of our closest living evolutionary relatives.s
to Cognitive Development in Chimpanzees -- Sociocognitive Development in Chimpanzees: A Synthesis of Laboratory Work and Fieldwork -- Behavioral and Physical Foundation -- A New Comparative Perspective on Prenatal Motor Behaviors: Preliminary Research with Four-Dimensional Ultrasonography -- Cognitive Abilities Before Birth: Learning and Long-Lasting Memory in a Chimpanzee Fetus -- Spindle Neurons in the Anterior Cingulate Cortex of Humans and Great Apes -- Descent of the Larynx in Chimpanzees: Mosaic and Multiple-Step Evolution of the Foundations for Human Speech -- Understanding the Growth Pattern of Chimpanzees: Does It Conserve the Pattern of the Common Ancestor of Humans and Chimpanzees? -- The Application of a Human Personality Test to Chimpanzees and Survey of Polymorphism in Genes Relating to Neurotransmitters and Hormones -- Communication and Mother-Infant Relationship -- Evolutionary Origins of the Human Mother-Infant Relationship -- Development of Facial Information Processing in Nonhuman Primates -- Development of Joint Attention in Infant Chimpanzees -- Food Sharing and Referencing Behavior in Chimpanzee Mother and Infant -- Development of Chimpanzee Social Cognition in the First 2 Years of Life -- Social Cognition: Imitation and Understanding Others -- Chimpanzee Learning and Transmission of Tool Use to Fish for Honey -- How and When Do Chimpanzees Acquire the Ability to Imitate? -- Yawning: An Opening into Empathy? -- How Social Influences Affect Food Neophobia in Captive Chimpanzees: A Comparative Approach -- Tactical Deception and Understanding of Others in Chimpanzees -- Conceptual Cognition -- Early Spontaneous Categorization in Primate Infants$1 (BChimpanzees, Humans, and Japanese Macaques$1 (Bwith the Familiarization-Novelty Preference Task -- Processing of Shadow Information in Chimpanzee (Pan troglodytes) and Human (Homo sapiens) Infants -- Color Recognition in Chimpanzees (Pan troglodytes) -- Auditory-Visual Crossmodal Representations of Species-Specific Vocalizations -- Spontaneous Categorization of Natural Objects in Chimpanzees -- Cognitive Enrichment in Chimpanzees: An Approach of Welfare Entailing an Animal$1 (Bs Entire Resources -- Tools and Culture -- Cognitive Development in Apes and Humans Assessed by Object Manipulation -- Token Use by Chimpanzees (Pan troglodytes): Choice, Metatool, and Cost -- Behavioral Repertoire of Tool Use in the Wild Chimpanzees at Bossou -- Ant Dipping in Chimpanzees: An Example of How Microecological Variables, Tool Use, and Culture Reflect the Cognitive Abilities of Chimpanzees -- Ontogeny and Cultural Propagation of Tool Use by Wild Chimpanzees at Bossou, Guinea: Case Studies in Nut Cracking and Leaf Folding.s
Keywords: Life sciences; Behavioral sciences; Zoology; Cognitive psychology; Life Sciences; Zoology; Behavioral Sciences; Cognitive Psychology; Electronic books